Servant Leadership and Innovative Work Behavior Among Civil Servants - Feoh, Novia Christine (Journal of Mental Health and Social Rehabilitation, 2024)
Public sector organizations vision is what prompts civil servants to engage in innovative work environment in order to enhance quality of public service. Servant leadership considered as leadership style that consistent within public sector values to help others, thus employees encouraged to engage in innovative work behavior if they find purpose and meaning in their work. This study aims to examine the role of work meaningfulness as a mediator in the relationship between servant leadership and innovative work behavior of civil servants Data collection for the study was conducted online involving 270 civil servants from various fields. Participants were recruited by purposive sampling method. Instrument of this study consist of the Servant Leadership Behavior Scale-6 (SLBS-6), Innovative Work Behavior Scale and The Work and Meaningful Inventory (WAMI). The data analysis in this study using Simple Mediation Analysis. The results showed that work meaningfulness significantly had a mediating effect on servant leadership on innovative work behavior (β = 0.523; p < 0.001). These results demonstrated that having employees' meaningful experiences during working would increase the role of contextual factors (servant leadership) toward innovative work behavior of civil servants.